SURE: Developing Learners’ Language Awareness through Pragmatics Instruction in the EFL Classroom - Rita Erlinda (Proceedings of ISELT FBS Universitas Negeri Padang, 2014)
A large number of English language learners in Indonesia tend to be recognised as ‘fluent fools’ learners. They can make all correct sentences following the grammar rules but cannot communicate in appropriate manner. The phenomenon of this ‘incompetent learners’ has been observed as a result of the absence of learners’ language awareness. Activities aimed at raising learners’ pragmatic competence and activies offering opportunities for communicative practice can be used as a way out of this faulty. The goal of this paper is to discuss activities utilized in pragmatic instruction. It has acronym name—SURE (See, Use, Review and Expeprience). Hopefully, this strategy will enable learners gradually to gain how language works and how to use language appropriate to a variety of communicative settings.